LITERACY SOCIALIZATION ON CYBER BULLYING PREVENTION AMONG STUDENTS OF SMP NEGERI 3 BILAH HULU - Syahputra, Robi; Prayoga, Yudi; Halim, Abd. (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Cyberbullying is an action taken by a person or group of people against another individual through text messages, pictures/photos, or videos that tend to humiliate and harass. The purpose of this service is to provide an understanding of the impact caused by students' negligence in using social media, increase students' knowledge of intelligence in responding to the world of social media, and increase self-awareness of wisdom in using social media. The location of the service is at SMP Negeri 3 Bilah Hulu, the subject of the service related to the socialization of the impact of cyberbullying on teenagers is teenagers who use social media services or platforms. Most of the teenage respondents said that cyberbullying was inappropriate behavior among teenagers, was an act of crime, harmed others, and endangered others. They also understand behavioral indicators that lead to cyberbullying behavior.